Sintering of dezincified α‐brass - Vollet, D. [UNESP]; Craievich, A. F.; Reich, R. (Wiley, 1981)
The formation and shrinkage of the porosity developed in dezincified α‐brass is studied by means of small angle X‐ray scattering and optical microscopy. Most of the coarse and submicroscopic voids, which are present in dezincified alloys, are eliminated by heat treatment at high temperature. The mechanism which explains the experimental kinetics of sintering is related to the migration of grain boundaries during the heat treatment. Copyright © 1981 WILEY‐VCH Verlag GmbH & Co. KGaA